Layered Intercalation Materials. Issue 25 (13th May 2021) - Zhou, Jingyuan; Lin, Zhaoyang; Ren, Huaying; Duan, Xidong; Shakir, Imran; Huang, Yu; Duan, Xiangfeng
Abstract: 2D layered materials typically feature strong in‐plane covalent chemical bonding within each atomic layer and weak out‐of‐plane van der Waals (vdW) interactions between adjacent layers. The non‐bonding nature between neighboring layers naturally results in a vdW gap, in which various foreign species may be inserted without breaking the in‐plane covalent bonds. By tailoring the composition, size, structure, and electronic properties of the intercalated guest species and the hosting layered materials, an expansive family of layered intercalation materials may be produced with highly variable compositional and structural features as well as widely tunable physical/chemical properties, invoking unprecedented opportunities in fundamental studies of property modulation and potential applications in diverse technologies, including electronics, optics, superconductors, thermoelectrics, catalysis, and energy storage. Here, the principles and protocols for various intercalation methods, including wet chemical intercalation, gas‐phase intercalation, electrochemical intercalation, and ion‐exchange intercalation, are comprehensively reviewed and how the intercalated species alter the crystal structure and the interlayer coupling of the host 2D layered materials, introducing unusual physical and chemical properties and enabling devices with superior performance or unique functions, is discussed. To conclude, a brief summary on future research opportunities and emerging challenges in the layered intercalation materials is given. Abstract : The intercalation of layered materials produces a rich class of materials with tunable structural and electronic properties for both fundamental studies and practical technologies. The key intercalation methods for preparing layered intercalation materials are summarized, the associated modulation of multiple properties is reviewed, and further prospects regarding the future challenges and opportunities in layered intercalation materials are considered.